Differential Coping Strategies in Response to Salinity Challenge in Olive Flounder - Zeng, Junjia; Herbert, Neill A.; Lu, Weiqun (Frontiers in Physiology, 2019)
To examine how different fish coping strategies respond to salinity challenge, olive flounder (Paralichthys olivaceus) with active coping style (AC) and passive coping style (PC) were transferred from seawater (SW) to freshwater (FW) and their behaviour and physiology were analysed. Different behavioural coping strategies, in terms of escape and feeding tendencies, were confirmed in AC and PC fish without FW exposure. Differences in swimming distance between AC and PC flounder were then assessed after 1 and 2 days of FW transfer. Plasma parameters and branchial gene expression were also determined 2, 5, 8 and 14 days after transfer, with comparisons between AC and PC fish and against a SW-acclimated control group. The results showed that: (1) PC flounder exhibited a significant reduction in swimming activity, while AC flounder significantly increased locomotion 2 days after transfer. (2) The plasma osmolality and plasma ionic (Na+ and Cl-) concentration of FW-acclimated PC flounder declined in a continuous fashion over time but this contrasted against the plasma parameters of AC flounder which fluctuated below the baseline level of a SW-acclimated control group. (3) The expression of NKA-α1 and NHE-3-like mRNA in PC flounder gill increased significantly from 5 days, but the expression of these two genes in AC flounder only increased after 8 days of transfer. (4) There were no remarkable differences observed in Rhcg expressions between AC and PC flounder. This study indicates for the first time that PC flounder adopt a “freeze-passive tolerance” strategy while AC flounder adopt a “flight-active resistance” defence strategy in response to salinity challenge.